THE RELATIONSHIP BETWEEN RETURN ON ASSETS AND FIRM SIZE IN INFLUENCING THE LEVELING OF COMPANY PROFITS - Nugrahini Kusumawati; Jaka Wijaya Kusuma (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2022)
This study aimed to examine the influence of a company's characteristics on income smoothing practices among listed companies on the Indonesian Stock Exchange. The factors being discussed were return on assets and firm size. Index Eckel is used to determining income smoothing. The study used 11 companies listed on the Indonesia Stock Exchange between 2012 and 2015. The hypothesis was tested using multiple regression. The first hypothesis examined the influence of return on assets on income smoothing practice. The second hypothesis was used to investigate the impact of firm size on income smoothing. The third hypothesis reviewed the effect of return on assets and firm size on income smoothing. The result of this study indicated that 11 out of 20 companies which were used as samples committed to income smoothing. The multiple regression output showed that return on asset and firm size does not significantly influence income smoothing.Keywords: ROA, Firm Size, Company Profits